2021
DOI: 10.1038/s41467-021-24288-1
|View full text |Cite
|
Sign up to set email alerts
|

Induction chemotherapy followed by definitive chemoradiotherapy versus chemoradiotherapy alone in esophageal squamous cell carcinoma: a randomized phase II trial

Abstract: This randomized phase II trial aims to compare the efficacy and safety of induction chemotherapy followed by definitive chemoradiotherapy (CRT) versus CRT alone in patients with esophageal squamous cell carcinoma (ESCC) unsuitable for surgery (N = 110). The primary outcome was overall response rate (ORR), whereas the secondary outcome was overall survival. This trial did not meet pre-specified endpoints. The ORR was 74.5% in the induction chemotherapy group versus 61.8% in the CRT alone group (P = 0.152). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…Liu et al. ( 14 ) also observed that patients who responded to IC had improved survival in the post-hoc analysis. Thirdly, histological types and tumor biological characteristics between ESCC and EAC are heterogeneous.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Liu et al. ( 14 ) also observed that patients who responded to IC had improved survival in the post-hoc analysis. Thirdly, histological types and tumor biological characteristics between ESCC and EAC are heterogeneous.…”
Section: Discussionmentioning
confidence: 88%
“…The 1-year OS rate was significantly higher in patients who were treated with IC-CCRT (HR 0.445, 95% CI 0.286–0.693; p < 0.001; Figure 2 ). In addition, three studies analyzed 3-year OS rate of the two groups ( 12 14 ). There was no significant difference in 2-year OS rate (HR 0.803, 95% CI 0.589–1.095; p = 0.166; Figure 2 ) and 3-year OS rate (HR 1.065, 95% CI 0.789–1.439; p = 0.680; Figure 2 ) between the two groups.…”
Section: Resultsmentioning
confidence: 99%
“…A randomized phase II study suggested that the incidence of grades 3–4 neutropenia of preoperative I-CCRT using oxaliplatin/capecitabine or carboplatin/paclitaxel for resectable esophageal adenocarcinoma was 2.6% (1/38) and 21.4% [9/42] ( p = 0.011) ( 25 ). Another randomized phase II trial demonstrated that the incidence of grade 3 or 4 neutropenia of I-CCRT and CCRT alone with DP in ESCC was 18.2% and 7.3%, respectively ( p = 0.151) ( 26 ). There were no significant differences in rates of other grades 3–5 hematological adverse events between groups were observed ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another randomized phase II trial demonstrated that the incidence of grade 3 or 4 neutropenia of I-CCRT and CCRT alone with DP in ESCC was 18.2% and 7.3%, respectively ( p = 0.151) ( 26 ). There were no significant differences in rates of other grades 3–5 hematological adverse events between groups were observed ( 26 ). Simoni et al.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy destroys the cancer cells growing faster than healthy cells or inhibiting their metastasis. 1,2 Because this process occurs non-specifically, an additional attack on rapidly dividing normal cells is a fatal disadvantage. The limitations of conventional chemotherapy have led to the development of smart nanocarrier systems.…”
Section: Introductionmentioning
confidence: 99%